Dietary free glutamine supplementation to increase physiological responses and survival rate of clown loach juvenile, Chromobotia macracanthus Bleeker, 1852 - Siti Murniasih; Dedi Jusadi; Mia Setiawati; Sri Nuryati (Jurnal Iktiologi Indonesia, 2019)
Clown loach Chromobotia macracanthus is one of Indonesian native species and as a key species for ornamental aquaculture. The problem in mass production of this species are the low of growth rate which causes a long period of rearing and low of survival rate. The purpose of the present study was to evaluate free glutamine supplementation at different doses in diet to increase physiological response, growth performance and survival rate of clown loach. Expe-rimental diets contained four different free glutamine levels, viz 0, 1, 2 and 3%. These diets were given to six repli-cate groups of 50 juvenile clown loaches. The fish were reared in each aquarium with dimensions of 40×30×30 cm3 for 60 days. Fish were fed four times a day at satiation. Parameters observed including intestinal glutamine concen-tration, villous and intestinal morphometry, intestinal protease activity, feed efficiency, nutrient retention, growth performance, survival rate, superoxide dismutase (SOD) activity, and malondialdehyde (MDA). The results showed that supplementation of 1% free glutamine significantly affected the morphometry of villi. The length and surface area of villi at a dose of 1% showed the highest values i.e., 320.44 ± 10.39 μm and 27,046.79 ± 250.54 μm2, respect-ively. The 1% dose also had a significant effect on protease activity (13.57 ± 1.92 mg units of protein-1) compared to the 0% dose. The 2% dose showed the highest SOD activity (0.82 ± 0.07 mg protein-1 unit) and the lowest MDA level was found at a dose of 3% (0.25 ± 0.02 nmol mg protein-1). Feed consumption with the supplementation of free glutamine has a significant effect on survival rate with the highest value reached 97.00 ± 1.00%, but no significant effect on intestinal morphometry, feed efficiency, nutrient retention and growth performance. Dietary with the sup-plementation of free glutamine is not able to improve growth performance, but can improve the physiological res-ponse and survival rate. Abstrak Ikan botia merupakan salah satu spesies asli Indonesia. Permasalahan dalam budi daya ikan ini adalah pertumbuhan yang lambat dan sintasan yang rendah. Penelitian ini bertujuan untuk mengevaluasi penambahan glutamin bebas de-ngan beberapa level dosis pada pakan terhadap respons fisiologis, kinerja pertumbuhan, dan sintasan ikan botia. Pene-litian menggunakan rancangan acak lengkap, terdiri atas empat perlakuan dengan enam ulangan. Perlakuan berupa penambahan glutamin bebas pada pakan komersial dengan dosis berbeda yaitu 0, 1, 2, dan 3%. Ikan uji yang diguna-kan adalah yuwana ikan botia umur 40 hari, dipelihara dalam akuarium berukuran 40x30x30cm3 sebanyak 24 unit dengan padat tebar 50 ekor per akuarium. Pakan diberikan selama 60 hari dengan frekuensi pemberian empat kali se-hari secara at satiation. Parameter yang diamati meliputi konsentrasi glutamin usus, morfometri vili dan usus, aktivi-tas protease usus, efisiensi pakan, retensi nutrien, pertumbuhan, sintasan, aktivitas superoxide dismutase (SOD), serta malon-dialdehyde (MDA). Hasil penelitian menunjukkan bahwa penambahan glutamin bebas 1% menunjukkan nilai paling tinggi untuk parameter panjang dan luas permukaan vili yaitu 320,44±10,39 µm dan 27.046,79±250,54 µm2. Dosis 1% menghasilkan pengaruh signifikan terhadap aktivitas protease (13,57±1,92 unit mg protein-1) dibandingkan dosis 0%. Perlakuan dosis 2% menunjukkan aktivitas SOD (0,82±0,07 unit mg protein-1) paling tinggi, sedangkan ka-dar MDA paling rendah terdapat pada dosis 3% (0,25±0,02 nmol mg protein-1). Konsumsi pakan dengan penambahan glutamin bebas berpengaruh nyata terhadap sintasan dengan nilai tertinggi 97,00±1,00%, tetapi tidak berpengaruh nyata terhadap morfometri usus, efisiensi pakan, retensi nutrien, dan pertumbuhan. Penambahan glutamin bebas da-lam pakan belum mampu meningkatkan kinerja pertumbuhan, namun mampu meningkatkan respons fisiologis dan sintasan ikan botia.